PENERAPAN MODEL PEMBELAJARAN BCCT (BEYOND CENTERS AND CIRCLE TIME) DI TKIT AL-MUMTAZ PONTIANAK - Fatimah, Dayang Srilia; Ali, Muhamad; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe aim of this research is to determine the application of the BCCT learning model at TKIT Al-Mumtaz Pontianak. The research method was a desctriptive with a form of qualitative research. The subject of this research were 5 teachers. The data were collected by using observation, interviews and documentation, with  tool of data collection in the form of observation guidance, interview guides and documentation. Meanwhile, analysis of the data using reduction, presentation and conclusion drawing. Based on the finding and discussion, it generally concluded that planning, implementing and evaluating the BCCT learning model has been implemented quite well. From the conclusion above, it can be specifically as follows: (1) the teacher trains child’s mentality to dare to communicate in role play. (2) the teacher develops the child’s ability to explore natural materials that they rarely find at home. (3) the teacher develops the basic development of them such as, recognize letters, numbers, read and write therefor they are ready for the next level. (4) the teacher makes activities by playing blocks so the children have the ability to solve the problem. (5) the teacher teachs religion, children are trained to carry out god’s order.Keywords: Description, Motivation in Learning